SYNYHETIC MEASURE AS PART OF THE ASSESSMENT OF SPATIAL DISPARITIES OF THE NATURAL ENVIRONMENT IN THE ŚWIĘTOKRZYSKIE VOIVODESHIP - Przybytniowski, Jarosław Wenancjusz; Dziekański, Paweł; Michalski, Mark (Management and Administration Journal, 2020)
The aim of this research was to indicate the possibilities of using synthetic measure to find and analyse spatial disparities of the natural environment in 102 diagnostic communities of the Świętokrzyskie Voivodeship as a peripheral area. The research was conducted on the basis of selected diagnostic features. The data presented refer to the years 2009, 2012 and 2015 and come from the Local Data Bank. Bearing in mind the research aim, the following hypothesis was formed: The use of proper synthetic measures makes it possible to recognise spatial disparities which appear in the natural environment. This paper is a continuation of the work entitled: Synyhetic Measure Used as Assessment of Spatial Disparities of the Natural Environment (Przybytniowski, Dziekański, 2019). The analysis of the natural environment of municipalities occurs through human activities, and having a direct impact on the environment (indirectly related to the environment).